Asymptomatic Chronic Stanford A Aortic Dissection after Coronary Artery Bypass Surgery - Muñoz, Juan (2020)
Acute Stanford A aortic dissection rarely makes a transition to the chronic state naturally, due to its high mortality. We present a rare case of chronic Stanford A aortic dissection post surgery, in a patient who remained stable for more than 1 year, and subsequently presented chest pain.